POLA ASUH DAN POLA KOMUNIKASI ORANG TUA DALAM MENUMBUHKAN KEPRIBADIAN ANAK DI BAWAH UMUR 15 TAHUN - putri, hany lidya; Ulya, Waziratun Mila'il; Sulistyo, Zuhrifa Putri (Jurnal Psikologi : Media Ilmiah Psikologi, 2024)
Parents have a very important role in the growth of a child, which is very necessary communication between the child and the parent well. Because it is a key that can grow personality in a child especially in children under the age of 15, with the role and pattern of communication of good parents then will generate a good personality also in the child. The aim of this study is to know the role of good communication between parents and children in growing good personalities in children below 15 years of age at SMPIT Darul Muqarrabin. This research uses a qualitative approach, that is, an approach done to the subject of research to an event, the author's position as an instrument of qualitative method. Data obtained in words, and sentences. The data came from the interview. From the results of interviews with five informants who are the parents of the student of SMPIT Darul Muqarrabin. Parents do not choose authoritarian and free communication patterns because the parents seem selfish toward their children and already know the impact on their children with authoritarian and free patterns.